Mammary analogue secretory carcinoma of the salivary glands: a diagnostic dilemma. Issue 3 (April 2017) - Hindocha, N.; Wilson, M.H.; Pring, M.; Hughes, C.W.; Thomas, S.J.
Abstract: Mammary analogue secretory carcinoma (MASC) is a recently identified salivary gland neoplasm that can mimic other salivary gland tumours such as acinic cell carcinoma and cystadenocarcinoma. It is distinguished from these by differences in immunohistochemical profile and the identification of an ETV6-NTRK3 translocation (12;15)(p13;q25), which is also found in secretory carcinomas of the breast. Previous publications have suggested that MASC tumours have similar biological behaviour to acinic cell carcinoma. We report two cases of MASC that affected the upper lip, and showed an infiltrative and locally aggressive growth pattern that required several operations to ensure clearance of microscopic tumour cells.